Unpacking Barriers to Digital Innovation: How Consumer Innovation Resistance and Brand Hate Accelerate the Spread of Negative Word-of-Mouth - Kholiludin, Ahmad; Yolanda Masnita; Kurniawati (Universitas Muhammadiyah Pontianak, 2026)
Digital innovation may trigger consumer resistance and negative word-of-mouth (NWOM) due to functional, psychological, and emotional barriers. This study examines the effects of innovation barriers and brand hate on consumer innovation resistance (CIR) and NWOM in Indonesian digital services. Data from 170 purposively selected users were analyzed using PLS-SEM. Risk barrier, image barrier, and brand hate positively influence CIR and NWOM, whereas value barrier is insignificant and tradition barrier shows a significant negative effect. CIR mediates the relationships between these barriers and NWOM. The findings highlight the importance of reducing perceived risks, improving technology image, and managing negative brand emotions.